Early Detection of Post-transplant Lymphoproliferative Disorder by Head and Neck Manifestations - Sisi Tian; Christopher Vuong; Justin Calvert; Justin McLarty; Miguel Krishnan (Journal of Hematology and Oncology Research, 2016)
Introduction: Post-transplant lymphoproliferative disease (PTLD) is a collection of conditions associated with abnormal proliferation of lymphoid tissues in patients after solid organ transplants (SOT). Its clinical presentations are quite variable and non-specific. Otolaryngological signs and symptoms, manifested as adenotonsillar hypertrophy or cervical lymphadenopathy, may guide to early detection and treatment. Methods: We conducted a retrospective review of all pediatric SOT recipients with the diagnosis of PTLD, age 0-18, between 2005 and 2014 at the Loma Linda University Children’s Hospital. The patient’s age, type of organ transplant, immunosuppression, head and neck signs and symptoms, imaging modality, EBV status, histology as well as treatment regimen information were recorded. Results: A total of 21 pediatric patients were included in this retrospective review with a history of solid organ transplant and a diagnosis of PTLD. The most commonly associated type of transplanted organ is heart (57.1%), followed by kidneys (33.3%) and liver (9.5%). Neck swelling (28.6%) was the main head and neck complaint while one patient developed upper airway obstruction with respiratory distress. Cervical lymphadenopathy was found in 66.7% and tonsillar hypertrophy in 9.5% of the patients. Monomorphic PTLD (46.2%) was the most common pathological diagnosis, followed by reactive hyperplasia (30.8%), Hodgkin lymphoma (15.4%) and polymorphic PTLD (7.7%). Majority of the PTLD patients were treated with rituximab and cyclophosphamide combination therapy with and without prednisone. Conclusion: Adenotonsillectomy and cervical lymph node biopsies are easy to perform with low complication rates. They serve an important role in the armamentarium in the early detection of PTLD in its early stage, allowing prompt treatment and prevention of further progression.
Keywords: Lymphoproliferative